Assessment of Mothers’ Knowledge about Breastfeeding in Basra City - Hadeel H. Haider; Noor Hasan Mohamed Taqi; Nuha Muhsen Mhebis (Indonesian Journal on Health Science and Medicine, 2026)
General Background Breastfeeding is essential for child development and protects against infant mortality. Specific Background Human milk is the recommended exclusive nutrient source during the first six months of life, making maternal understanding of proper lactation techniques crucial for successful child health outcomes. Knowledge Gap Although formal education generally correlates with better health literacy, it remains unclear why mothers with high educational attainment still display significant awareness gaps regarding optimal breastfeeding practices. Aims This study assessed mothers' knowledge about breastfeeding and evaluated their primary information sources within primary healthcare settings in Basra City. Results Out of 158 participants, 76.6 percent resided in urban areas and 46.2 percent completed college. Crucially, 79.7 percent of mothers exhibited poor breastfeeding knowledge, and 62 percent received only simple reassurance from health centers. Medical facilities were the most frequent knowledge source for 28 percent of respondents, followed closely by the internet at 27 percent, while family and friends accounted for 11 percent. Novelty This study reveals a critical paradox where high formal college education fails to translate into adequate breastfeeding literacy among urban housewives in Basra. Implications Primary healthcare centers must shift from basic reassurance to well-designed, structured prenatal and postnatal lactation counseling programs to rectify widespread institutional knowledge gaps. Keywords: Breastfeeding, Maternal Knowledge, Lactation Counseling, Public Health, Primary HealthcareKey Findings HighlightsWidespread knowledge deficiencies exist among mothers, with 79.7 percent demonstrating poor breastfeeding literacy.High formal college education does not guarantee adequate awareness regarding optimal infant feeding practices.Primary healthcare centers provide minimal counseling support, leaving the internet as a nearly equal source of maternal information.